Metal Atom-Decorated Carbon Nanomaterials for Enhancing Li-S/Se Batteries Performances: A Mini Review - Gu, Xingxing; Deng, Lan; Ren, Xiaolei (Frontiers in Energy Research, 2021)
Lithium-sulfur (Li-S) and lithium-selenium (Li-Se) batteries are both facing the cathode issues of low Coulombic efficiency and unstable cycling stability due to the severe shuttle effect of lithium polysulfides or lithium polyselenides. Simultaneously inhibiting polysulfides/polyselenides dissolution in organic electrolytes and propelling them conversion via introducing polar, catalytic materials has been proven as an effective strategy to enhance the durability of the Li-S and Li-Se batteries. In this mini review, we systematically introduce various metal atoms decorated carbon nanomaterials that how to enhance the electrochemical performances of Li-S and Li-Se batteries by inhibiting the polysulfides/polyselenides shuttle phenomenon as well as catalytic them quick redox conversions. We also briefly conclude the drawbacks and bottlenecks of this kind materials used in Li-S and Li-Se batteries.